Pemanfaatan Google Sites sebagai Media Pembelajaran Digital Interaktif dalam Pembelajaran Matematika: Studi Kasus di Sekolah Menengah Atas : Utilizing Google Sites as an Interactive Digital Learning Media in Mathematics Learning: A Case Study in High School - Jelita Fuji Khaebibah; Surya Amami Pramuditya (Information Technology and Science (ITScience), 2026)
The development of digital technology is driving the transformation of learning toward the use of interactive, flexible, and student-centred learning media, particularly in mathematics instruction in Senior High Schools (SMA). Challenges that are still frequently encountered include limited face-to-face time, limited variety of learning media, and the need for readily accessible independent learning resources. This study aims to analyse the accessibility of Google Sites-based mathematics learning media and to evaluate user feedback and experience with these media, developed as a digital learning hub. The study used a descriptive-evaluative approach with a single-case design. The research subjects included three peers serving as expert assessors, one mathematics teacher, and three high school students as actual users. The research instrument was a Likert-scale questionnaire covering technical, pedagogical, aesthetic, and interactivity aspects, supplemented by open-ended comments. Data were analysed descriptively and thematically. The results showed that the media received an average peer-assessment score of 4.25, categorised as